ZAKAT BESI TUA PERSPEKTIF MASLAHAH (Studi Kasus di Desa Tanjung Jati Kecamatan Kamal Kabupaten Bangkalan) - Ahmad Kholili (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2016)
Employers scrap metal in Tanjungjati Kamal Bangkalan pay zakat results can be scrap metal scrap itself without specifying the exact number of kilograms treasures of Zakat and alms execution time was erratic, sometimes carried out once a year. Although, in fact, a maslahah on charity goods in the form of scrap metal which is more inclined to the maslahah mursalah, because it is a benefit that does not exist for the proposition determined by Islamic law, but can diqiyaskan with the provisions of zakat trade and zakat of wealth. Akan tetapi, persepsi dan pelaksanaan zakat besi tua di Desa Tanjung However, the perception and implementation of scrap metal at Tanjungjati zakat is not in accordance with Islamic law for the implementation of zakat, scrap metal businesses do not calculate in advance what the treasure they consider the charity that had reached the nisab or not. Moreover, zakat target was not based on a categorization that has been set according to Islamic law, but by their own way.